Association of Thr12Ser polymorphism in mitochondrial transcription factor A TFAM gene with coronary artery disease - T. V. Zheikova; M. V. Golubenko; S. V. Buikin; O. A. Makeeva; A. A. Lezhnev; I. V. Tsimbalyuk; V. M. Shipulin; V. P. Puzyryov (Бюллетень сибирской медицины, 2012)
In this study we genotyped polymorphism Thr12Ser (rs1937) in TFAM gene in two groups: patients with coronary artery disease and control group (people from Tomsk population). For genotyping was used restriction fragment length polymorphism. We have found significant higher genotype CC frequency in men with coronary artery disease — 4.52% compared with control men — 0.45% (χ2 = 6.315; р = 0.043; OR = 10.45). Thus genotype CC is associated with coronary artery disease in men fromTomsk population.